2021
DOI: 10.1155/2021/6627254
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Trace Element Contamination in Drinking Water and Agricultural Soil: A Study in Selected Chronic Kidney Disease of Unknown Etiology (CKDu) Endemic Areas in Sri Lanka

Abstract: Unexplained or unclear etiology of chronic kidney disease (CKDu) has been reported in Sri Lanka’s North Central Province (NCP) for more than two decades. Meanwhile, high exposure to heavy metals/metalloids and their accumulation are recognized as the origin of many acute and chronic diseases in certain vulnerable human tissues including kidneys. This study evaluates the contamination status of heavy metals/metalloids of the drinking water and agricultural soil in two CKDu endemic areas compared with a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…When copper is found in the soil, it binds strongly to organic matter and minerals. Generally speaking, it is accepted that copper has low mobility in soils [20]. However, as in the case of the P1 profile, Baize [2] demonstrated that the transfer of copper could take place particularly in acidic soils such as in certain podzosols because of the pH which impacts its mobility through its speciation.…”
Section: Physicochemical Properties Of Soils and Their Tme Concentrat...mentioning
confidence: 99%
See 1 more Smart Citation
“…When copper is found in the soil, it binds strongly to organic matter and minerals. Generally speaking, it is accepted that copper has low mobility in soils [20]. However, as in the case of the P1 profile, Baize [2] demonstrated that the transfer of copper could take place particularly in acidic soils such as in certain podzosols because of the pH which impacts its mobility through its speciation.…”
Section: Physicochemical Properties Of Soils and Their Tme Concentrat...mentioning
confidence: 99%
“…This suggests that there is multiple contamination of this sludge by TMEs. The pollution index greater than 1 in the sludge of the basins would be due to the high concentrations of TMEs coming from the accumulation of waste of all kinds, the less clayey texture of the sludge (%A<30) and the content of organic matter [20] because its very low clay texture facilitates the mobility of TMEs towards the outlets which are surface water and the surrounding soil. As a result, the layers of clay minerals are not numerous enough to capture the metal ions in the environment [7].…”
Section: Sludge and Soil Pollution Index By Heavy Metalsmentioning
confidence: 99%
“…But the CKDu disease patients had been reduced from 2011 to 2014 due to shift of country towards the organic farming. Ministry of Health had launched a plan called 'Towards a Toxin Free Country' for promotion of organic farming and health of public (Perera et al, 2021).…”
Section: Healthmentioning
confidence: 99%
“…This poor environmental condition has clearly disrupted the community health. The water sources used to daily activities certainly affect the body's metabolism or organs, such as kidney damage ( 5 ). The kidney damage result in the inability of the glomerular kidney to filter and reabsorb food substances, such as protein.…”
Section: Introductionmentioning
confidence: 99%